Gastrointestinal Tolerability With Oliceridine, A Novel µ Receptor G Protein Pathway Selective (µ-GPS) Modulator [4H]. Issue 1 (May 2017) - Steinberg, Adam C.; Soergel, David; Burt, David; Skobieranda, Franck
Abstract : INTRODUCTION: Conventional opioids bind to μ receptors and non-selectively activate two intracellular signaling pathways. One (G protein pathway) is associated with analgesia. The second (β-arrestin pathway) is associated with opioid-related adverse events and inhibition of G protein-mediated analgesia. Oliceridine (TRV130) is a novel µ receptor G protein Pathway Selective (µ-GPS) modulator that activates G protein while causing low β-arrestin recruitment to the μ receptor. This novel mechanism of action could lead to a differentiated therapeutic profile of rapid/effective analgesia with improved safety and gastrointestinal tolerability than conventional opioids. METHODS: Subjects in a Phase 2 randomized control clinical trial with moderate-to-severe acute pain following abdominoplasty were assigned into one of 4 IV PCA treatment groups. All treatment groups incorporated a 6-minute PCA lockout interval and were: volume-matched placebo, morphine regimen (4 mg loading; 1 mg demand), oliceridine regimen A (1.5 mg loading; 0.10 mg demand), oliceridine regimen B (1.5 mg loading; 0.35 mg demand). RESULTS: Of the 200 subjects, demographics and baseline characteristics were similar between treatment groups. At equianalgesic dose, both regimens of oliceridine were associated with a significantly lower percentage of patients who experienced both nausea and vomiting versus morphine (13% and 13% versus 39%; p less than 0.05). No serious adverse events (AEs) reported for the 4 groups. CONCLUSION: In this study, both regimens of oliceridine had a significantly lower prevalence of gastrointestinal AEs versus morphine. This suggests that oliceridine may widen the therapeutic window between rapid/effective analgesia and gastrointestinal dysfunction. These results may extrapolate to obstetric and gynecologic procedures but further investigation is warranted.